Optimized primers and other critical conditions for efficient fusion PCR to generate knockout vectors in filamentous fungi. - Nicholas Harrison; Brad Cavinder; Jeffrey P. Townsend; Frances Trail (Fungal Genetics Reports, 2013)
Methods to streamline functional studies of large numbers of genes are essential to fully utilize the significant genomic resources now available for fungi. Fusion PCR is often used to join pieces of DNA together, particularly in the construction of DNA fragments for gene replacement in fungi. Here we present high-efficiency primers which reliably direct fusion and amplification to generate constructs for gene knockouts. Addendum: The authors communicated this omission post publication: We inadvertently left out the 3HS sequence with which we had such great success. The 5HS sequence, as seen in Figure 2D, is 5'-AGTCGACGACAACTACCATCGATCTGACG. The 3HS sequence which was missing from the original paper is 5'-ACACTGGTGACGGCTAACCAGAACTGTCA.